OP0212 The Effects of SGC Stimulators on Wound Healing in the Tight Skin (TSK-1) Mouse Skin Fibrosis Model. (9th June 2015) - Haasbach, E.; Beyer, C.; Distler, J.; Sandner, P.
Abstract : Background: Systemic sclerosis (SSc) is a systemic, autoimmune mediated, orphan disease with significantly increased morbidity and mortality and a low quality of life. Besides skin fibrosis, SSc causes alterations of the microvasculature and severe peripheral vasculopathies, including perivascular fibrosis, Raynaud's phenomena and the formation of digital ulcers (DU). Many drugs, proposed to have anti-fibrotic effects, inhibit wound healing and might thus further complicate the healing of ischemic ulcers in SSc. Objectives: Although sGC stimulators like Riociguat inhibit the release of collagen in experimental models of fibrosis, they also improve acral perfusion due to their vasodilatory effects. We thus speculated that the vasodilatory effects of Riociguat may balance its inhibitory effects on collagen release in wound healing and may thus not negatively affect wound healing in SSc patients. The aim of these studies was to characterize the effects of the sGC stimulators BAY 63-2521 (Riociguat) and BAY 41-2272 on wound healing in the tsk-1 mouse skin fibrosis model. Methods: The tight-skin (tsk-1) mouse model of SSc was used to evaluate the effects of the sGC stimulators BAY 63-2521 (Riociguat) and BAY 41-2272 on wound closure in mice with skin fibrosis. During anesthesia, WT mice and tsk-1 mice were bilaterally punched, establishing a defined round wound with 4 mm in diameter. WT mice and tsk-1 mice were treated with either placebo, BAY 63-2521 or BAY 41-2272 and efficacy was measured by reduction of wound area, 3 days after punching. Results: In WT mice a reduction in wound size by 68%±2% was found after 3 days. Compared to WT mice, wound closure was significantly attenuated in tsk-1 mice with a reduction in wound size of only 52%±2%. Treatment with the sGC stimulator BAY 63-2521 (Riociguat) had no influence on wound healing in WT mice. In tsk-1 mice both sGC stimulators caused a dose-dependent and significant improvement of wound healing. Wound sizes were reduced by 59%±4%, 65%±3% ( p <0.05) and 70%±2% ( p <0.0001) with 0.3, 1 and 3 mg/kg BAY 63-2521, respectively. And tsk-1 mice treated with 1 and 3 mg/kg BAY 41-2272 showed a reduction of 64%±3% and 73%±2% ( p <0.0005). Conclusions: These data imply that the sGC stimulators BAY 63-2521 (Riociguat) and BAY 41-2272 could become and efficacious treatment option for SSc-related vasculopathies, especially for prevention and healing of DU. Disclosure of Interest: E. Haasbach Employee of: Bayer Pharma AG, C. Beyer: None declared, J. Distler: None declared, P. Sandner Employee of: Bayer Pharma AG